Rapid test for lung maturity, based on spectroscopy of gastric aspirate, predicted respiratory distress syndrome with high sensitivity. (20th December 2016) - Verder, Henrik; Heiring, Christian; Clark, Howard; Sweet, David; Jessen, Torben E.; Ebbesen, Finn; Björklund, Lars J.; Andreasson, Bengt; Bender, Lars; Bertelsen, Aksel; Dahl, Marianne; Eschen, Christian; et al.
Abstract: Aim: Respiratory distress syndrome (RDS) is a major cause of mortality and morbidity in premature infants. By the time symptoms appear, it may already be too late to prevent a severe course, with bronchopulmonary dysplasia or mortality. We aimed to develop a rapid test of lung maturity for targeting surfactant supplementation. Methods: Concentrations of the most surface‐active lung phospholipid dipalmitoylphosphatidylcholine and sphingomyelin in gastric aspirates from premature infants were measured by mass spectrometry and expressed as the lecithin/sphingomyelin ratio (L/S). The same aspirates were analysed with mid‐infrared spectroscopy. Subsequently, L/S was measured in gastric aspirates and oropharyngeal secretions from another group of premature infants using spectroscopy and the results were compared with RDS development. The 10‐minute analysis required 10 μL of aspirate. Results: An L/S algorithm was developed based on 89 aspirates. Subsequently, gastric aspirates were sampled in 136 infants of 24–31 weeks of gestation and 61 (45%) developed RDS. The cut‐off value of L/S was 2.2, sensitivity was 92%, and specificity was 73%. In 59 cases, the oropharyngeal secretions had less valid L/S than gastric aspirate results. Conclusion: Our rapid test for lung maturity, based on spectroscopy of gastric aspirate, predicted RDS with high sensitivity.